Yahoo! Web analytics tracking, reporting, and analyzing for data-driven insights - Mortensen, Dennis R., 1972-; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2009)
"Yahoo! Web Analytics teaches readers how to collect data, report on that data, and derive useful insights using Yahoo!'s free Web analytics tool . This detailed resource from Yahoo!'s Director of Data Insights discusses the why of Web analytics as well as the how while revealing secrets and tricks not documented elsewhere. The thorough book also offers step-by-step instructions and advanced techniques on everything from using data collection groupings to creating compelling data visualizations. It's a must-read for all analytics professionals and those who want to be"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Yahoo! Web analytics; Web usage mining -- Computer programs; Internet users -- Statistics -- Data processing; Web sites -- Statistics -- Data processing; Consumers' preferences -- Data processing; Electronic books